Mechanical hysteresis and damage evolution in C/SiC composites under fatigue loading at room and elevated temperatures. Issue 6 (13th June 2019) - Li, Longbiao; Reynaud, Pascal; Fantozzi, Gilbert
Abstract: In this paper, the mechanical hysteresis and damage evolution in C/SiC ceramic matrix composites (CMCs) under cyclic tension‐tension fatigue loading at room and elevated temperatures in air and in inert atmosphere and different loading frequencies are investigated. The fatigue hysteresis loops models considering multiple matrix cracking modes are developed to establish the relationships between fatigue hysteresis loops, fatigue hysteresis dissipated energy, and fiber/matrix interface shear stress. The evolution of fatigue hysteresis dissipated energy and interface shear stress vs applied cycles is analyzed. It was found that the interface shear stress degradation rate increases with fatigue peak stress, and loading frequency from 40 to 375 Hz.